Implementasi Pembelajaran Matematika dengan Teori Belajar Bruner untuk Mempelajari Perkalian Siswa Kelas II di SD N Gilingsari Temanggung dalam Program Kampus Mengajar - Agustin, Sara Sarita; Pratini, Haniek Sri (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2025)
Covid-19 has resulted in a concerning condition of education in Indonesia, prompting the government to initiate the "Kampus Mengajar" program to help revive education in the country. The "Kampus Mengajar" program is part of the "Merdeka Belajar - Kampus Merdeka" (MBKM) initiative organized by the Ministry of Education and Culture (Kemendikbud). The activities of the "Kampus Mengajar" focus on enhancing literacy and numeracy skills, assisting school administration, and promoting the use of technology in schools. One of the target schools for the "Kampus Mengajar" program is SD Negeri Gilingsari Temanggung. The author implemented Bruner's learning theory to aid students at SD Negeri Gilingsari in learning mathematics, specifically multiplication skills. Bruner's learning theory was chosen because it emphasizes the use of representative forms to facilitate students' understanding of mathematics. The learning process is carried out using teaching aids such as cups and corn kernels to represent the multiplication of numbers. The aim of this research is to describe the impact of using Bruner's learning theory to teach multiplication tables from one to ten to second-grade students at SD Negeri Gilingsari.This research adopts a qualitative research method, where the data obtained will be described in detail according to the real-life conditions. The research findings indicate that through learning with Bruner's learning theory, students' multiplication skills have improved. The students' development is demonstrated by their ability to comprehend multiplication as repeated addition